PENGARUH PROMOSI PENJUALAN DAN SERVICESCAPE TERHADAP IMPULSE BUYING DENGAN SHOPPING EMOTION SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA KONSUMEN HYPERMART MALANG TOWN SQURE) - Salsa Nabila; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to look at the effect of sales promotion and servicescape on impulsive purchases with emotional shopping as an intervening variable. The data used in this study is the poor Hypermart consumer town square. This study used as many as 100 samples. The sampling technique uses accidental sampling. The method used is the path analysis method to determine data analysis using the path analysis method and using the validity test, reliability test, normality test, t test and sobel test using the SPSS version 14.0 application. From the results of the study, it shows that sales promotion and servicescape have a positive and significant effect on emotional shopping, sales promotion and servicescape has a positive and significant effect on impulsive purchases, and shopping emotions have a positive and significant effect on impulsive purchases.Key Word: Sales Promotion, Servicescape, Shopping Emotion, Impulse Buying